A noção de sujeito para além das gramáticas e a perspectiva de alunos dos ensinos fundamental e médio: teoria x prática - Marília Lacerda Mendonça da Silva (2021)
Under the functionalist perspective of linguistic studies, this research aims to investigate different notions attributed to the grammatical category of subject by elementary and high school students, in syntactic analyses, since there are some semantic, syntactic and pragmatic divergences between what is observed in practice and what is prescribed by normative grammars. In this sense, the work aims at (a) investigating in which contexts of manifestation of the subject students have more difficulty in identifying it, (b) attesting whether subjects regarded as prototypical tend to be more easily recognized and (c) verifying which notion of subject is the most used by students to identify the term in a linguistic structure. It was possible to detect the notions of subject most used by them in the syntactic analysis and the main difficulties displayed in identifying the term. The results revealed that students have greater difficulty in recognizing non-prototypical subjects or subjects with a low degree of prototypicality, in addition to subjects realized by more complex structures.